2010
DOI: 10.1038/labinvest.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus facilitates the malignant potential of immortalized epithelial cells: from latent genome to viral production and maintenance

Abstract: Epstein-Barr virus (EBV) is closely associated with several malignancies, including nasopharyngeal carcinoma. To investigate the EBV activity in tumor development, we tried to establish a malignant model of EBV-infected cells in nude mice. On the basis of the Maxi-EBV system, a human embryonic kidney epithelial cell line (293) with a low malignant potential was used for a stable EBV genome infection. The derived cell line, termed 293-EBV, exhibited obvious morphological transformation and significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 50 publications
2
61
0
Order By: Relevance
“…HEK-293 cells stably transfected with the p2089 plasmid (293-EBV) were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal calf serum (Therm, UK) (12). An immortalized normal nasopharyngeal epithelial cell line NP69 was cultured in keratinocyte serum-free medium (gifted by the Chinese University of Hong Kong) (13).…”
Section: Ethicsmentioning
confidence: 99%
See 2 more Smart Citations
“…HEK-293 cells stably transfected with the p2089 plasmid (293-EBV) were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal calf serum (Therm, UK) (12). An immortalized normal nasopharyngeal epithelial cell line NP69 was cultured in keratinocyte serum-free medium (gifted by the Chinese University of Hong Kong) (13).…”
Section: Ethicsmentioning
confidence: 99%
“…The viral genes BZLF1 and BALF4 in the pcDNA3.1(+) vector were transiently transfected into the 293-EBV cells (12,16), and the GFP-EBV was released from the transfected cells into the supernatant due to expression of BZLF1 and BALF4 which was induced by lytic replication of the 293-EBV cells (17). After 72 h, the supernatant was collected and filtered through a 0.45-mm pore-size filter.…”
Section: The Established Model Of Ebv-infected Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting were performed as described previously [8]. Protein samples were subject to electrophoresis in SDS-PAGE gels and analyzed ABSTRACT: Epstein-Barr virus nuclear antigen 1 (EBNA1) is essential for EBV episome's replication and mitotic segregation.…”
Section: Western Blottingmentioning
confidence: 99%
“…This method provided the basis for whole-genome level investigations into the mechanism by which EBV contributes to NPC development [104]. We found that infection with the whole genome of EBV significantly promoted the growth and malignancy of epithelial cells [105] and activated NF-κB and MAPK signaling [106].…”
Section: Ebv and Nanobacteriamentioning
confidence: 99%